Tropical Cyclone Future Projections - Murakami, Hiroyuki (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The increasing frequency of tropical-cyclone damage has attracted public interest regarding the impact of global warming on tropical cyclone activity. Although the global mean temperature has been rising since the 20th century, the detection and attribution of any climate change in tropical cyclone activity remain uncertain due to the limited length of reliable observations. A number of previous studies have reported projected future changes in tropical cyclone frequency. However, there remains substantial uncertainty regarding future changes in tropical cyclone activity and their impact. The publication of this Special Issue aims to minimize uncertainty in the possible future changes in tropical cyclone activity. Individual papers solicited for this Special Issue focus on (1) quantifying change in the characteristics of tropical cyclones in a warmer climate; (2) observed climate change in tropical cyclone activity; (3) assessing tropical cyclone risks, mitigations, and adaptations for future climate change; (4) assessing potential future changes in the impact of tropical cyclones on oceans (e.g., marine biochemistry, marine ecosystem, storm surges, and sea level rise); (5) theoretical or experimental studies related to the tropical cyclone climate.